2014
DOI: 10.1088/1751-8113/47/31/315204
|View full text |Cite
|
Sign up to set email alerts
|

Traveling waves of the regularized short pulse equation

Abstract: Abstract. In the present work, we revisit the so-called regularized short pulse equation (RSPE) and, in particular, explore the traveling wave solutions of this model. We theoretically analyze and numerically evolve two sets of such solutions. First, using a fixed point iteration scheme, we numerically integrate the equation to find solitary waves. It is found that these solutions are well approximated by a truncated series of hyperbolic secants. The dependence of the soliton's parameters (height, width, etc) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Apart from these exact solutions, approximate peakon-like and breather-like solitary waves, which can be regarded as ultrashort gap solitons in nonlinear MMs, were also presented [29]. Furthermore, in [37], both localized and extended waveforms that arise in the SPE were considered, and direct simulations showed that the most robust solution is the breathertype one (although some of the single-hump variants of the periodic solutions may be preserved during evolution as well) -see also relevant work in Reference [32]. Notice that, in Reference [37], multi-peakon, multi-breather, and multi-hump waveforms were found to be subject to symmetry breaking instabilities, thus, being less robust during propagation.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from these exact solutions, approximate peakon-like and breather-like solitary waves, which can be regarded as ultrashort gap solitons in nonlinear MMs, were also presented [29]. Furthermore, in [37], both localized and extended waveforms that arise in the SPE were considered, and direct simulations showed that the most robust solution is the breathertype one (although some of the single-hump variants of the periodic solutions may be preserved during evolution as well) -see also relevant work in Reference [32]. Notice that, in Reference [37], multi-peakon, multi-breather, and multi-hump waveforms were found to be subject to symmetry breaking instabilities, thus, being less robust during propagation.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Such corrections, play an important regularizing role on the SPE, which, otherwise, admits multi-valued (so-called "loop") solutions [31]. The RSPE, on the other hand, admits smooth traveling-wave solutions [30], which have structure similar to solitary waves of the NLS model [32]. In our system, however, such a 4th-order derivative term can not be obtained, because of the assumed form of the permittivity and permeability (cf.…”
Section: Propagation In the Frequency Bandgapsmentioning
confidence: 99%
“…It is now well understood how band-limted functions can possess local oscillations arbitrarily faster than their fastest Fourier components [1][2][3][4][5][6]. This is the mathematical phenomenon of superoscillation, with applications to physics [7]; examples are superresolution microscopy [8][9][10], and a possible mechanism for heating the solar corona [11].…”
Section: Introductionmentioning
confidence: 99%
“…Τέτοιες διορθώσεις, παίζουν σημαντικό ρόλο στην SPE, η οποία, διαφορετικά, δέχεται λύσεις πολλαπλών τιμών (αποκαλούμενες «loop») [71]. Η RSPE έχει λύσεις ομαλούς παλμούς οδεύοντος κύματος [68], που έχουν παρόμοια δομή με τα μοναδικά κύματα NLS [77]. Ωστόσο, στο υπό εξέταση υλικό Drude-Lorentz δεν μπορεί να ενσωματωθεί ένας τέτοιος όρος παραγώγου 4-ης τάξης, λόγω της θεωρούμενης συναρτησιακής μορφής της επιτρεπτότητας και διαπερατότητας [βλ.…”
Section: μη γραμμικός εντοπισμός ηλεκτρομαγνητικών κυμάτων σε ηλεκτρομαγνητικές ζώνες χασμάτωνunclassified